Problem Analysis of Working Refugees in Makassar City - Slamet Sampurno Soewondo; Kadarudin Kadarudin (Jurnal Ilmiah Kebijakan Hukum, 2022)
The refugee problem in Makassar City happens to the working refugee. Some of them work as barbers in a barbershop and as construction workers. The refugees who work are often caught in raids conducted by the Makassar immigration detention center (Rudenim) as a part of supervisory duties. By working, refugees are found guilty of violatin g the Regulation of the Director General of Immigration Number IMI-0352.GR.02.07 of 2016. This paper contains an analysis of the questions that arise regarding the problems of working refugees. For example, what are the rules that refugees must obey? What are the forms of supervision for refugees in Indonesia? What are the main problems experienced by refugees that caused them to violate the prohibition to work? The purpose of writing this paper is to find out the regulation that must be obeyed by refugees and the form of supervision for them who temporarily stay in Indonesia. In addition, this paper also aims to analyze the forms of violations committed by the refugees. This study used qualitative approach to analyze primary and secondary legal materials. The results of the study show that one of the rules that must be obeyed by refugees who temporarily stay in Indonesia is the prohibition of doing any activities to earn wages. The form of supervision is carried out by re-examining the identity and documents of refugees and asking for information as outlined in the examination official report.  As a suggestion regarding the management of refugees, the Makassar Rudenim can do refugee monitoring more intensively and provide reporting space for citizens who have information related to violations committed by the refugees.